Bactericidal antibodies against hypervirulent Neisseria meningitidis C field strains following MenC-CRM or MenACWY-CRM priming and MenACWY-CRM booster in children. Issue 5 (4th May 2021) - Giuliani, Marzia Monica; Biolchi, Alessia; Keshavan, Pavitra; Moriondo, Maria; Tomei, Sara; Santini, Laura; Mori, Elena; Brozzi, Alessandro; Bodini, Margherita; Nieddu, Francesco; Ricci, Silvia; Mzolo, Thembile; et al.
ABSTRACT: An increase in invasive meningococcal disease (IMD) incidence was observed in Tuscany in 2015/2016, mainly due to hypervirulent clonal complex (cc) 11 strains. In a post-hoc analysis, we assessed bactericidal activity of antibodies in sera from children primed with MenACWY-CRM or MenC-CRM conjugate vaccines and receiving a MenACWY-CRM booster dose against 5 meningococcal C (MenC) strains isolated from IMD cases. Sera collected from 90 infants/toddlers who participated in a phase III, open-label study (NCT00667602) and its extension (NCT01345721) were tested by serum bactericidal activity assay with human complement (hSBA). Children were primed with either MenACWY-CRM at 6–8 and 12 months of age (group 2_MenACWY; N = 30), MenACWY-CRM (group 1_MenACWY; N = 30), or MenC-CRM at 12 months of age (group 1_MenC; N = 30); all received MenACWY-CRM booster dose at 22–45 months of age. Four tested strains (FI001–FI004) were C:P1.5–1, 10-8:F3-6:ST-11 (cc11) and 1 (FI005) was C:P1.7–4, 14-6:F3-9:ST-1031 (cc334). Overall, immune responses tended to be higher against Fl002–FI004 than Fl001 and Fl005. Geometric mean titers were high in group 2_MenACWY (range: 94.8 [FI005]–588.1 [FI004]) and very high post-boosting with MenACWY-CRM in all groups (176.9 [FI005]–3911.0 [FI004]). Seroresponse rates tended to be higher in group 1_MenC (33.3% [FI005]–93.3% [FI004]) than in group 1_MenACWY (16.7% [FI005]–73.3% [FI004]). Irrespective of strains tested or the identity/number of priming doses, ≥96.7% of children had hSBA titers ≥1:8 post-MenACWY-CRM booster dose. MenACWY-CRM and MenC-CRM elicited bactericidal antibodies and immunological memory against hypervirulent cc11 and cc334 MenC strains responsible for IMD outbreaks.